ON MERCENARIES IN WORLD POLITICS - GOGA, Ramona (Studia Universitatis Babes-Bolyai Studia Europaea, 2023)
The purpose of the present paper is to emphasize the way mercenaries integrated in the world politics. It offers an overview of the historical context, highlighting short details about the early appearance of mercenary troops who, although not yet bearing that name, acted in the same way. What is more, it pursues the evolution of mercenaries from their very beginning to the contemporary era, making a short stop to the Middle Ages, and then to the pre-modern period. Furthermore, it describes the metamorphosis of mercenaries in the contemporary period, giving birth to the new ´dogs of war’ under different names. However, these transformations came with behavioural changes as well. They changed their attitude and their chaotic actions on the battlefield, fulfilling, sometimes, a different role, but for the same purpose, which labelled them as ‘new mercenaries’ from the outset.